2013
DOI: 10.1080/09712119.2012.739084
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition,in vitrodigestibility and kinetics of fermentation of whole-crop forage from 18 different varieties of oat (Avena sativaL.)

Abstract: The aim of this study was to compare the yield of forage and the yield of digestible organic matter as well as chemical composition and kinetics of fermentation of forage produced from 18 different varieties of oat (Avena Sativa L.) grown under the same agronomic condition. Dry matter and organic matter digestibility were determined using in vitro two-stage method and gas production technique was used to measure the kinetics of fermentation of forage from different varieties. Yield of forages varied significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
5
2
2
Order By: Relevance
“…Generally, in vitro gas production are useful in estimating metabolizable energy, organic matter digestibility and short-chain fatty acids of the feed [ 42 ]. Values for in vitro organic matter digestibility recorded in this study for different forages of S. scabra accessions are higher than the values for varieties of Avena sativa L. reported by Kafilzadeh and Heidary [ 43 ]. The range of 68.4 to 75.6% of IVOMD recorded in this study for different forages of S. scabra accessions indicate good digestibility of forages despite the fact that accessions were harvested at maturity.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Generally, in vitro gas production are useful in estimating metabolizable energy, organic matter digestibility and short-chain fatty acids of the feed [ 42 ]. Values for in vitro organic matter digestibility recorded in this study for different forages of S. scabra accessions are higher than the values for varieties of Avena sativa L. reported by Kafilzadeh and Heidary [ 43 ]. The range of 68.4 to 75.6% of IVOMD recorded in this study for different forages of S. scabra accessions indicate good digestibility of forages despite the fact that accessions were harvested at maturity.…”
Section: Discussioncontrasting
confidence: 84%
“…The range of 68.4 to 75.6% of IVOMD recorded in this study for different forages of S. scabra accessions indicate good digestibility of forages despite the fact that accessions were harvested at maturity. The calculated value for ME in present study were observed to be higher than those of Avena sativa L. and Vicia sativa L. as reported by Kafilzadeh and Heidary [ 43 ] and Huang et al [ 44 ], respectively. However, they were in the range of values for alfalfa hay as recorded by Abas et al [ 45 ].…”
Section: Discussioncontrasting
confidence: 45%
“…The fermentation products are negatively related to the fiber contents [40], and positively correlated with non-fibrous carbohydrate (NFC) content [41] of substrates. Lactate, an intermediary product, is mainly produced from the fermentation of easily fermentable feed, and then metabolized to VFAs, the end products of rumen microbial fermentation [23].…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con Geatchew et al (1998) la cinética de producción de gas depende de las proporciones relativas de proporciones de partículas solubles, insolubles pero degradables e indegradables del alimento. Kafilzadeh and Heidary, (2013), quienes midieron por medio de la técnica de producción de gas la cinética de fermentación de 18 variedades de avena en Irán, tuvieron una media en cuanto a la fracción A (soluble) de 60.7 ml/g, 10.1 y 16.6 ml menos en comparación con los tratamientos de AN y ANT, respectivamente. PME tuvo entre 8 y 18 % más mL de gas en la fracción A que AN y ANT, esto debe a que el contenido de FDN en los tratamientos con avena es 10 % mayor y por tanto la cantidad de fracciones solubles es menor (Martínez-Loperena et al, 2011).…”
Section: Producción De Gas In Vitrounclassified
“…PME tuvo entre 8 y 18 % más mL de gas en la fracción A que AN y ANT, esto debe a que el contenido de FDN en los tratamientos con avena es 10 % mayor y por tanto la cantidad de fracciones solubles es menor (Martínez-Loperena et al, 2011). En cuanto al tiempo lag, Kafilzadeh and Heidary, (2013) obtuvieron una media de 0.702, lo que resulta en una tasa de fermentación menor en comparación con este trabajo, donde se obtuvieron medias de 4.46 para el rebrote de avena (Etapa 1) y de 9.1 en la evaluación de avena como ensilado (Etapa 2). Cabe señalar que Kafilzadeh and Heidary, (2013) evaluaron avena cuando esta se encontraba en estado lechoso masoso (GS 83, de acuerdo a la escala Zadoks para la evaluación de etapas de crecimiento de los cereales), en cambio en este trabajo la avena se encontraba en estado de rebrote, lo que se puede deber a que el material soluble puede no ser degradado rápidamente por los microorganismos del rumen al exceder la máxima capacidad de estos microorganismos para usar el sustrato de forma rápida, y el tiempo para degradar la fracción insoluble resultaría mayor (Dijkstra et al, 2002).…”
Section: Producción De Gas In Vitrounclassified